2016
DOI: 10.1371/journal.pone.0166133
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Nausea, Vomiting, Fatigue and Health-Related Quality of Life of Women in Early Pregnancy: The Generation R Study

Abstract: The objective of this study was to evaluate the independent associations between nausea, vomiting, fatigue and health-related quality of life of women in early pregnancy in the Generation R study, which is a prospective mother and child cohort. Analyses were based on 5079 women in early pregnancy in the Rotterdam area, the Netherlands. The information on nausea, vomiting and fatigue in the previous three months was measured in the questionnaire at enrollment, as well as potential confounders (i.e., maternal/ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 43 publications
6
49
0
2
Order By: Relevance
“…Regarding QoL, our SF‐12 findings are similar to Lacasse et al . and Bai et al . who also found NVP versus no NVP women performed substantially worse in the physical domain (−13% versus −16% in our study), and lower than the corresponding scores by Chan et al .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding QoL, our SF‐12 findings are similar to Lacasse et al . and Bai et al . who also found NVP versus no NVP women performed substantially worse in the physical domain (−13% versus −16% in our study), and lower than the corresponding scores by Chan et al .…”
Section: Discussionsupporting
confidence: 89%
“…Limitations include modest sample size, and convenience sampling of women from a single institution in Sydney's eastern suburbs (advantaged socioeconomic area), potentially not reflecting QoL effects on the wider Australian maternity population. However, overseas evidence suggest the influence of demographics on QoL in NVP is minor compared to the influence of symptom severity, so our findings likely still apply to the broader population.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the physical condition of pregnancy, NVP and HG also negatively affect the mental health, quality of life, and functional capacity of women [6]. In severe cases, fetal development might also be affected.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that links this condition to alternation in a variety of hormones, including estrogen, progesterone, placental prostaglandin E2, and thyroid-stimulating hormone [1]. In addition, studies have shown that NVP may also be linked with psychological disturbances, including eating disorders, neurotic tendencies, hysteria, and rejection of pregnancy, as well as anxiety and depression with psychological stress related to poverty and marital conflicts [6,7]. From these psychological disturbances, anxiety and depression exert a special importance, because apart from being a cause, it can also be a consequence of NVP.…”
Section: Introductionmentioning
confidence: 99%
“…Mild morning sickness symptoms in early pregnancy were associated with decreased positive emotion from early to middle pregnancy. Pregnant women with severe nausea and vomiting are known to have lower health-related QOL compared to women not experiencing these symptoms (Bai et al 2016). Moreover, the severity of nausea is associated with lower physical and mental QOL among pregnant women (Lacasse et al 2008;McCarthy et al 2011).…”
Section: Discussionmentioning
confidence: 99%